3D Vertically Aligned and Interconnected Porous Carbon Nanosheets as Sulfur Immobilizers for High Performance Lithium‐Sulfur Batteries. Issue 12 (9th April 2016) - Rehman, Sarish; Gu, Xingxing; Khan, Kishwar; Mahmood, Nasir; Yang, Wenlong; Huang, Xiaoxiao; Guo, Shaojun; Hou, Yanglong
Abstract : A unique nanostructure of 3D and vertically aligned and interconnected porous carbon nanosheets (3D‐VCNs) is demonstrated by a simple carbonization of agar. The key feature of 3D‐VCNs is that they possess numerous 3D channels with macrovoids and mesopores, leading to high surface area of 1750 m 2 g −1, which play an important role in loading large amount of sulfur, while vertically aligned microporous carbon nanosheets act as the multilayered physical barrier against polysulfides anions and prevent their dissolution in the electrolyte due to strong adsorption during cycling process. As a result, the 3D hybrid (3D‐S‐VCNs) infiltered with 68.3 wt% sulfur exhibits a high and stable reversible capacity of 844 mAh g −1 at the current density of 837 mA g −1 with excellent Coulombic efficiency ≈100%, capacity retention of ≈80.3% over 300 cycles, and good rate ability (the reversible capacity of 738 mAh g −1 at the high current density of 3340 mA g −1 ). The present work highlights the vital role of the introduction of 3D carbon nanosheets with macrovoids and mesopores in enhancing the performance of LSBs. Abstract : Integrated 3D vertically aligned and interconnected porous carbon nanosheets are fabricated to demonstrate the effect of physical adsorption of soluble polysulfides via 3D‐S‐VCNs with large macrovoid and mesoporous channels on enhancing the electrochemical performance of lithium‐sulfur batteries (LSBs).